Avaliação do desempenho e características relacionadas ao grau de infecção por helmintos de bovinos da raça nelore - Pacheco, Tiago Marolato [UNESP] (2015)
The objective was to identify different categories of animals inside a Nellore heifers herd according to their degree of helminth infection, correlating data from fecal examinations, hematological, serological and productive performance in order to evaluate the difference between the categories of infection of these animals. 100 Nellore females were evaluated, averaging eight months old. Were evaluated: coproparasitological analysis, blood test for hematologic changes, serological analysis for IgG levels, measurements of fat thickness and performance. The animals were identified in three groups according to their degree of helminth infection: resistant, resilient or susceptible. Data were analyzed with the help of BioEstat Software, version 5. The animals resistant weaned heavier. When analyzed the seasonal period there is less weight gain of susceptible animals during the rainy season. The group proved less likely to packed cell volume. We conclude that the animals which were more affected by gender Haemonchus spp. and Oesophagostomum spp., with a decrease in cell volume. All categories showed a similar growth performance during the experiment, but due to the seasonality only animals susceptible were influenced. Taking into account that the susceptible individuals harbor a larger number of gastrointestinal nematodes, the selection of these animals would be a good alternative to reduce the use of anti-helminthic